ANALISIS KINERJA TENAGA AHLI DALAM MENINGKATKAN KINERJA DI FRAKSI GERINDRA DPR RI - Fahira, Raihany Dinda; Basuki, Johanes (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2025)
This study aims to analyze the performance of expert staff in the Gerindra Party Faction of the Indonesian House of Representatives (DPR RI) using Bernardin and Russell’s performance theory. The research focuses on six key performance indicators: quality, quantity, timeliness, cost-effectiveness, independence, and interpersonal impact. A qualitative approach was employed, with data collected through in-depth interviews with expert staff and faction members. The findings reveal that the performance of expert staff in the Gerindra Faction is largely influenced by their ability to produce accurate outputs that meet faction needs, complete tasks within deadlines, and utilize resources efficiently. Furthermore, expert staff are expected to work independently, take initiative, and establish effective communication and collaboration with both legislators and colleagues. The study concludes that expert staff play a crucial role in supporting the effectiveness of the faction’s legislative, oversight, and budgeting functions. The research recommends continuous capacity building, stronger work standards, and a more structured performance evaluation system to enhance the quality of expert staff’s work. Keywords: DPR RI; Expert Staff; Gerindra Faction; Performance